Double duty: using a PEG tube to address gastrogastric fistula and biliary drainage in a patient after Roux-en-Y - Preeyati Chopra, MBBS; Ashwariya Ohri, MBBS; Mayank Goyal, MBBS; Navtej S. Buttar, MD (VideoGIE, 2025)
Background and Aims: Gastrogastric fistula (GGF) is a known rare adverse event after gastric bypass surgery. Management of refractory GGF, either surgical or endoscopic, is associated with poor long-term results. There is limited evidence on the successful management of refractory GGF with endoscopy. Methods: A 62-year-old female patient status post Roux-en-Y gastric bypass presented with symptoms of aspiration. She not was responsive to repeated endoscopic and laparoscopic methods for fistula closure, which made her unfit for surgical intervention. We decided to proceed with an endoscopic attempt for fistula management. On EGD, a 15-mm fistula between the gastric pouch and the remnant stomach was seen. A 24F PEG tube bumper with a 25-mm diameter was folded with a grasping device and inserted in the 15-mm fistula, such that the bumper fully covered the fistula. The bumper was sutured to the surrounding mucosa in a purse string fashion. The open tip of the PEG tube was driven into the Roux limb and sutured in the jejunum to prevent migration of the tube. This achieved the dual purpose of closing the site of the fistula with the PEG bumper while securing a draining tube to prevent aspiration of the bile reflux in the gastric pouch. Results: A postprocedure fluoroscopy demonstrated no evidence of a fistula. At follow-up, the patient reported no reflux and complete resolution of symptoms. The patient is planned for a yearly replacement of the PEG tube, given multiple comorbidities and a hostile abdomen due to previous procedures that make her unfit for surgical intervention. Conclusions: In a patient who did not respond to repeated endoscopic and laparoscopic methods for management, we describe a novel endoscopic technique for management of refractory GGF using a PEG tube serving the dual purpose of plug and drain after Roux-en-Y gastric bypass surgery.